The use of advanced e-technologies in state governance - L. N. Alekseeva (Вестник Российского экономического университета имени Г. В. Плеханова)
Local, state and federal bodies of power use e-technologies (from automation to artificial intellect) in order to improve the life of the population. The new generation of computer complexes excel people in the intellect quality as a strategic tool of the economic development of the country and upgrading of its state governance. The article shows how to use technologies to raise efficiency at working places and to improve the life of the population. Principle opportunities of using e-technologies, big data and artificial intellect in state governance were studied. Prospects of processing the natural language by computers and building smart cities were described. In spite of enormous positive effect of introducing e-technologies, each new technology implies an additional risk. Such potential risks were estimated. Key trends of the future development of artificial intellect systems were analyzed, as they become a serious tool of process management. Today states face a new choice: should the managerial operations be completely automated, can the job be distributed between people and devices or should it be carried out by people with the help of devices. State sectors creating advantages of automation use such technologies as big data analysis, artificial intellect and Internet of things. Opportunities of artificial intellect are real and endless and things that were earlier only theoretical concepts, today form practical solutions.